2015
DOI: 10.1194/jlr.m059444
|View full text |Cite
|
Sign up to set email alerts
|

A novel unsaturated fatty acid hydratase toward C16 to C22 fatty acids from Lactobacillus acidophilus

Abstract: This article is available online at http://www.jlr.org revealed that the metabolites of LA, 10-hydroxy-cis -12-octadecenoic acid and 13-hydroxy-cis -9-octadecenoic acid, were detected at higher levels in the intestines of specifi c pathogen-free (SPF) mice than in those of germ-free mice, indicating that gastrointestinal microbes play a role in modifying the FA profi le of their host mice.The physiological functions of 10-hydroxy FAs and their derivatives begin to become clear. 10-Hydroxy-cis -12-octadecenoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 29 publications
4
64
0
4
Order By: Relevance
“…Furthermore, although there are differences in the likelihood of use of adjuvant chemotherapy based on the factors such as socioeconomic status, the fairly homogenous nature of participants (health professionals) would likely increase the probability of at least standard therapy. [39,40] Comorbidities and access to health care may also confound our findings; however, given the population studied, we would expect the latter to be diminished. Moreover, although comorbidities have may influence overall survival, [41,42] such diseases are less likely to affect CRC-specific mortality, [43] the primary endpoint of this study.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, although there are differences in the likelihood of use of adjuvant chemotherapy based on the factors such as socioeconomic status, the fairly homogenous nature of participants (health professionals) would likely increase the probability of at least standard therapy. [39,40] Comorbidities and access to health care may also confound our findings; however, given the population studied, we would expect the latter to be diminished. Moreover, although comorbidities have may influence overall survival, [41,42] such diseases are less likely to affect CRC-specific mortality, [43] the primary endpoint of this study.…”
Section: Discussionmentioning
confidence: 82%
“…NRRL-2994 and Saccharomyces cerevisiae was ranging from 82 to 98%, while Nocardia aurantia ATCC 12674 only produced enantiomeric mixtures of ( R )- and ( S )-10-HSA (Yang et al 1993). For isolated FAHs, excellent ee values were reported in the case of OhyA (ee of 98% for ( R )-10-HSA from OA) (Engleder et al 2015), CLA-HY (ee > 99.9% for ( S )-10-hydroxy fatty acids from LA, α- and γ-linolenic acid (LnA) (Takeuchi et al 2014) and FA-HY1 from L. acidophilus NTV001 (ee > 99% for ( R )-13-hydroxy fatty acids from LA and α-LnA) (Hirata et al 2015). Contrary to the S. cerevisiae -mediated production of 10-HSA from OA (el-Sharkawy et al 1992; Yang et al 1993), more recent investigations are pointing towards hydration of OA by bacterial contaminants of employed yeast preparations (Brunner and Hintermann 2016; Serra and De Simeis 2017).…”
Section: Enzymes For Hydration and Their Propertiesmentioning
confidence: 99%
“…Oh and coworkes, however, have identified a new ∆12-hydratase from Lactobacillus acidophilus, which predominantly forms the 13-hydroxy derivative of linoleic acid [133,134]. In addition, Hirata and coworkers showed that the ∆12-hydratase from Lactobacillus not only converts C18 cis PUFAs, but also arachidonic acid (C20) and DHA (C22) into the corresponding 15-hydroxy fatty acid and the14-hydroxy fatty acids, respectively [135]. Moreover, recent reports on ∆9 hydratases processes with recombinant enzymes underline their potential applicability for the large-scale production of 10-hydroxy fatty acids derivatives.…”
Section: Fatty Acid Double Bond Hydratasesmentioning
confidence: 95%